Avaliação eletroneuromiográfica em pacientes com artrite reumatóide - Vasconcelos, José Tupinambá Sousa; Medeiros, Marta Maria Das Chagas; Cavalcanti, Mauro Furtado (My University, 2003)
Objective: to describe the peripheral neuromuscular system abnormalities in adult RA patients using electroneuromyography (ENM) in order to determinate their prevalence. Potential correlation between electroneuromyographic findings and demographic, clinical, laboratorial and radiological data was ako examined. Methods: sixty four adult RA patients were evaluated for demographic, clinical, laboratorial and radiological parameters, and ENM was performed in all of them. Results and conclusions: ENM abnormalities were found in 14 (21.9%) RA patients. Carpal tunnel syndrome (CTS), the most prevalent abnormality, was detected in 9 patients (14.1%) and peripheral polyneuropathy (PPN) was present in 8 patients (12.5%). PPN associated with CTS was observed in 3 patients (4.7%) and 1 patient (1.6%) presented PPN associated with ulnar nerve compression at the elbow. In half of the PPN cases, only sensitive neural Gbers were involved. In the other half, motor involvement was also detected. The primary pattern lesion was axonal loss in all PPN cases. Compressive neuropathy was present in 50% of PPN patients. There was statistically significant correlation between the presence of ENM abnormalities and the duration of disease (p < 0.001).
Electroneuromyographic evaluation in rheumatoid arthritis patients
Keywords: Carpal tunnel syndrome; Electroneuromyography; Rheumatoid arthritis